2021
DOI: 10.1021/acsami.1c08740
|View full text |Cite
|
Sign up to set email alerts
|

Quasicrystalline Coatings Exhibit Durable Low Interfacial Toughness with Ice

Abstract: Ice accretion can adversely impact many engineering structures in commercial and residential sectors. Although there are many reports of low-iceadhesion-strength materials, a scalable and durable deicing solution remains elusive, as ice detachment is dominated by interfacial toughness for large interfaces. In this work, durable metallic coatings based on Al-rich quasicrystalline alloys were prepared and applied on aluminum substrates using high-velocity oxyfuel thermal spray. X-ray diffraction patterns confirm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 33 publications
2
28
0
Order By: Relevance
“…Materials exhibiting low interfacial toughness (LIT) with ice represent a paradigm shift in how the adhesion between ice and a surface may be reduced, especially large (>cm) iced interfaces 45 , 46 . LIT materials minimize the strain energy necessary to propagate an interfacial crack between the ice and surface, enabling size-independent de-icing, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Materials exhibiting low interfacial toughness (LIT) with ice represent a paradigm shift in how the adhesion between ice and a surface may be reduced, especially large (>cm) iced interfaces 45 , 46 . LIT materials minimize the strain energy necessary to propagate an interfacial crack between the ice and surface, enabling size-independent de-icing, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…[28] Mohseni et al found that quasicrystalline coatings show excellent ice repellency even after being abraded, scratched, heated, UV-irradiated, and exposed to chemical contaminations, which are promising for real outdoor anti-icing application (Figure 3f). [59] Besides, Boinovich et al proposed a strategy by combining both laser processing and deposition of fluorooxysilanes to overcome main drawbacks and improve resistance to destroying atmospheric impacts. [60] In short, various rational designs (i.e., surface textures, preparation methods and anti-icing strategy based optimizations) have been developed to enhance the durability of passive AIM such that the AIM can be utilized for a long-term use in the outdoor anti-icing application.…”
Section: Shssmentioning
confidence: 99%
“…found that quasicrystalline coatings show excellent ice repellency even after being abraded, scratched, heated, UV‐irradiated, and exposed to chemical contaminations, which are promising for real outdoor anti‐icing application (Figure 3f). [ 59 ] Besides, Boinovich et al. proposed a strategy by combining both laser processing and deposition of fluorooxysilanes to overcome main drawbacks and improve resistance to destroying atmospheric impacts.…”
Section: Passive Aimmentioning
confidence: 99%
See 2 more Smart Citations